Zwroty ku przestrzeni w badaniach literackich – próba uporządkowania pojęć i podstawowe rozróżnienia - Gieba, Kamila (Przestrzenie Teorii, 2015)
An increased interest in space in the humanities can be referred to as a spatial, topographic or topological shift. This article is an attempt at organizing these concepts and defining the fundamental differences between them. Based on the findings of European and American researchers (including Edward Soja, Sigrid Weigel, Ernest W.B. Hess-Lüttich, and Joseph Hillis Miller) and a Polish literary scholar (Elizabeth Rybicka), the author tries to distinguish, and define the relationship, between spatial, topographic and topological shifts. This article was inspired by the terminological chaos in the Polish humanities.